Association of Knowledge and Quality of Life With the Intake of Dietary Supplements Among the Students - Majeed, Anushka; Khan, Iqra Hamid; Gohar, Awais; Shah, Fatima Iftikhar (Biological and Clinical Sciences Research Journal, 2025)
Dietary supplements refer to the products that contain vitamins, minerals, herbs, amino acids, oil supplements, or other substances intended to supplement the diet. Nutrient deficiencies are frequently addressed with dietary supplements. Supplements can fill in these gaps and ensure that you get enough nutrients. Objectives: The aim of the study was to assess the frequency of dietary supplement intake, to assess the association between knowledge and intake of dietary supplements and to assess the association of quality of life with the intake of dietary supplements among the university students. Methodology: It was an analytical cross-sectional study which was conducted among the students at the University of Lahore. Probability Simple Random Sampling was employed to select students of the departments, and the data was gathered through self-administrated questionnaire. The data was analyzed using SPSS version 25.0. Used SF-36 questionnaire to measure quality of life while a pre validated self-administered questionnaire was used to access the knowledge and intake of dietary supplements. Results: Data from 266 participants was collected. The frequency of dietary supplement use among students was 75.9%. Intake of dietary supplement was higher in females (71%) as compared to males (60.5%). Moreover, it revealed a significant association between the level of knowledge about dietary supplements with the intake of dietary supplements (p-value < 0.05). Intake of dietary supplement was higher among those students who have adequate knowledge regarding dietary supplements (88.1%) as compared to those who have inadequate knowledge regarding dietary supplements (73.7%). However, no significant difference was observed in the domains of quality of life between ds users and non-ds users. (p>0.05) except for physical functioning (p=0.041*). Conclusions: It was observed that the use of dietary supplements increases the physical functioning capacity of its users.